Fungsi Prefiks me-(N) dalam Cerita Populer Berjudul Antagonist Princess - Zulfa, Ilma (Deskripsi Bahasa, 2025)
The addition of the prefix {me-N} to a word does not only mean doing something. However, this addition has various grammatical meanings. The objectives of this research are (1) to describe the affixation of prefix {me-N}, (2) the function of prefix {me-N} as derivational or inflectional, and (3) the grammatical meaning of prefix {me-N} in the Antagonist Princess story. The data in this research are the prefix {me-N} in the popular story, "Antagonist Princess" by Reffa Renata on Wattpad, episodes 1 to 10. The data collection used a note-taking technique. The results of this research show that the prefix {me-N} in the popular story 'Antagonist Princes' episodes 1 to 10 contains at least 120 data points. The affixation in the form of prefix addition {me-N} is attached to the noun, adjective, and verb categories. The function of the prefix {me-N} is derivational from the category of noun word class to verb and adjective word class to verb. The inflectional function comes from the category of fixed verbs into verbs. There are seven categories of grammatical meaning from the addition of the prefix {me-N} in the Antagonist Princess story.